2020
DOI: 10.3390/toxics8040119
|View full text |Cite
|
Sign up to set email alerts
|

Does External Exposure of Glycidol-Related Chemicals Influence the Forming of the Hemoglobin Adduct, N-(2,3-dihydroxypropyl)valine, as a Biomarker of Internal Exposure to Glycidol?

Abstract: Glycidyl fatty acid esters (GE) are constituents of edible oils and fats, and are converted into glycidol, a genotoxic substance, in vivo. N-(2,3-dihydroxypropyl)valine (diHOPrVal), a hemoglobin adduct of glycidol, is used as a biomarker of glycidol and GE exposure. However, high background levels of diHOPrVal are not explained by daily dietary exposure to glycidol and GE. In the present study, several glycidol-related chemicals (glycidol, (±)-3-chloro-1,2-propanediol, glycidyl oleate, epichlorohydrin, propyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, in verifying the relationship between lipase activity and the release of glycidol from GEs, the lipase activity and diHOPrVal in blood were measured in C57/BL6J mice fed a HFD for 8 weeks. A previous study showed that when glycidyl oleate was administered to rats at 0.5 and 1.0 mmol/kg b.w., the level of diHOPrVal in the blood at 24 h was 419 ± 50 and 1055 ± 110 pmol/g globin, respectively [ 36 ]. Therefore, mice fed with HFD were orally administered glycidyl oleate dissolved in soybean oil at doses of 0, 0.1, 0.5, and 1.0 mmol/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in verifying the relationship between lipase activity and the release of glycidol from GEs, the lipase activity and diHOPrVal in blood were measured in C57/BL6J mice fed a HFD for 8 weeks. A previous study showed that when glycidyl oleate was administered to rats at 0.5 and 1.0 mmol/kg b.w., the level of diHOPrVal in the blood at 24 h was 419 ± 50 and 1055 ± 110 pmol/g globin, respectively [ 36 ]. Therefore, mice fed with HFD were orally administered glycidyl oleate dissolved in soybean oil at doses of 0, 0.1, 0.5, and 1.0 mmol/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
“…The 2,3-hydroxypropyl substituents are formed upon food treatment, they covalently attach into Val and were found as N-2, 3-dihydroxypropyl Val residues in hemoglobin. This derivative was considered as a marker in food examination [39]. Neither in this toxicological study nor in other cases [40] the enantiomerically pure gl derivatives were studied separately.…”
Section: Time-dependent Cellular Accumulationmentioning
confidence: 99%
“…In our previous study, diHOPrVal was not produced from chemicals other than glycidol or glycidol-related chemicals (epichlorohydrin, propylene oxide, 1-bromopropane, allyl alcohol, fructose, and glyceraldehyde), although a single dose of these chemicals was administered to rats (Shimamura et al, 2020).…”
Section: Several Chemicals Have Been Proposed As Possible Precursorsmentioning
confidence: 99%
“…In our previous study, diHOPrVal was not produced from chemicals other than glycidol or glycidol‐related chemicals (epichlorohydrin, propylene oxide, 1‐bromopropane, allyl alcohol, fructose, and glyceraldehyde), although a single dose of these chemicals was administered to rats (Shimamura et al., 2020 ). Humans are routinely exposed to these chemicals and it is possible that the amount of diHOPrVal produced is small following a single administration to experimental animals.…”
Section: Introductionmentioning
confidence: 99%